Estudo de caso de um professor participante do programa de formação contínua em serviço via internet Teachers´Links - Malacrida, Marta Janete (2006)
This dissertation was developed in the intersection of the research lines Language and Work, Language and Education and Language and Technology of the Applied Linguistics Programme. Its main objective was to analyze the practice of a Teacher who followed an In-service Programme of Continuous Education aimed at teachers of English in public schools in the State of São Paulo - Teachers Links - in order to see what of the Programme could be seen in his teaching. The teacher s classroom data and interviews with the researcher were analyzed with the purposes of evaluate the contributions of the Programme for the research participant. The main theoretical underpinning for the research is: Vygotsky, 1998; Celani, 2000 - 2003; Celani and Collins, 2003; Nóvoa, 1992; Gómes, 1992; Freire, 1996; Halliday, 1994 - 1985 - 1976; Eggins, 1994; Eggins and Slade, 1997; Thompson, 1996; Martin, 1994 among others. The research questions were: 1- What aspects of the Teachers Links Programme are present in the teacher s practice? 2- How does the teacher use knowledge he acquired in the Programme? 3- What are the signs that the teacher profited from the programme in his practice? 4- How does the teacher evaluate the program? The data was collected in a Public School in the State and in the data base of the Programme. The findings show the influence of course, in the teacher s practice, as well the representation he built of the program. The results also raise some suggestions to upgrade programme Teachers Links